Notes on six microcaddisfly species (Trichoptera: Hydroptilidae) recorded for Japan, one a newly described species - Ito, Tomiko; Shimura, Noriyoshi (Zootaxa, 2019)
Notes are provided for six microcaddisfly species (Trichoptera, Hydroptilidae) in the Japanese fauna. One is a new species, Hydroptila nago Ito sp. nov., described from southern Japan. The second and third, Hydroptila dorsoprocessuata Botosaneanu 1993, previously known from eastern Russia, and Hydroptila introspinata Zhou and Sun 2009, known from northeastern China and Korea, are recorded from Japan for the first time and redescribed. A fourth, Hydroptila parapiculata Yang and Xue 1994, is known from central and southeastern China and central Japan; the male is redescribed. By synonymizing Ugandatrichia shinshiroensis Ito et al. 2018, described from central Japan, with a Chinese species, Allotrichia rhynchophyllum Zhou et al. 2016, we record the genus Allotrichia McLachlan from Japan for the first time. For a sixth species, Stactobia distinguenda Nozaki and Botosaneanu 1996, previously known in Japan from the male only, the larva and its case are described.